Peningkatan Tanggung Jawab Dan Hasil Belajar Matematika Melalui Strategi Contextual Teaching And Learning Berbasis Investigasi (PTK Bagi Siswa Kelas VII Semester Gasal SMP Negeri 2 Gatak Sukoharjo Tahun Ajaran 2013/2014) - Susilo, Tri; , Prof. Dr. Sutama, M.Pd (2014)
This study aims to determine the increased responsibility and student learning outcomes through the implementation of strategies of Contextual Teaching and Learning (CTL)-based investigation. This research is evaluative research, including qualitative research based on function. With a design that is used is Classroom Action Research (CAR), which conducted the collaboration between mathematics teachers and researchers which is carried out in two Cycle. The data source is the teacher and the student . recipient of the action is the subject VII.B graders of SMP Negeri 2 Gatak Sukoharjo totaling 32 students. Data collection techniques used are observation, testing, field notes, and documentation. Data were analyzed with descriptive qualitative method of data flow is analyzed from the learning measures implemented and developed during the learning process. The results of the study are: 1) there is increased responsibility indicators seen from the increasing responsibilities include. a) execute and complete the task seriously than before action 21.87 % , Cycle I 46.87 %, Cycle II 68.75 %. b ) fulfill the promise of 37.5 % before treatment Cycle I 53.12 %, Cycle II 81.25 %. c ) willing to accept the consequences of his actions before the action of 12.5 %, Cycle I 40.62 %, Cycle II 62.5 % and 2 ) there is an increase in results learn math with indicators students who scored more than equal to 75 dar before the action of 28.12 %, Cycle I 43.75 %, Cycle II 68.75 %. This study concludes that the application of CTL -based investigation to increase the responsibility and learning outcomes of mathematics learnings.